Implications of Strategic Management in Increasing Sales (MSMEs) in Bekasi Regency - Sari, Putri Nawang; Purnamasari, Pupung (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This research aims to determine the implementation of the strategy of Increasing Micro, Small and Medium Enterprises (MSMEs). The research design uses qualitative descriptive, data collection by observation methods, in-depth interviews and documentation. The data collected from the informants is deliberately determined according to the needs (purposive sampling), the results relevant to the problem being researched are analyzed qualitatively through the process of data collection, data reduction and drawing conclusions. The purpose of this study is to know, describe and analyze the implementation of strategies in increasing SME sales and their supporting and inhibiting factors. This study uses a descriptive method with a qualitative approach with a focus on the problems are (1) Implementation of strategies in increasing sales of Micro, Small and Medium Enterprises. UKM) in Bekasi Regency, and (2) Supporting factors and inhibiting factors. The result of this study is that the implementation of the strategy has not gone well due to the dynamic real conditions of the field, so it requires flexible strategic management with supporting and inhibiting factors internally and externally. The advice given is Micro, Small and Medium Enterprises. UKM ) Bekasi Regency must be more active in improving and developing businesses